Executive Committee Minutes 2019-09-05 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 8/22/19 – Approved. Chair Report. Provost Report – given by K. Moranski. Vice Chair Report. Vice President for Student Affairs Report. Lecturer Conversion Presentation. From EPC: Discontinuance – Minor in Physical Sciences – approved as business for the Senate. Faculty Eligible for Emeritus Status – approved for the Senate's consent calendar. Discussion: Recent removal of FERP faculty from department RTP committees. APARC Report. EPC Report. FSAC Report. CFA Report. Senate Agenda approved. Last thoughts on any discussion.